What risk factors affect hospitalisation for confirmed pertussis cases among infants in the Czech Republic? - Liptáková, M; Špačková, M; Balasegaram, S; Malý, M; Kynčl, J; Fabiánová, K (Epidemiologie, mikrobiologie, imunologie, 2022)
BACKGROUND: We estimated what risk factors affect hospitalisation for confirmed pertussis cases among infants (child up to 1 year) in the Czech Republic based on data from the questionnaire-based enhanced surveillance system (ESS) in years 2015, 2017 and 2019. METHODS: Retrospective cohort study was conducted in which we assessed demographic, clinical data, vaccination status and risk/protective factors. Vaccination status was extracted from the electronic nationwide notification system (NNS). We performed descriptive, univariable and multivariable analysis using risk ratio (RR) and logistic regression with odds ratio (OR). RESULTS: A total of 104 confirmed cases (27, 13, 64) were reported in the ESS during 2015, 2017 and 2019. Most cases were in age group 1 month (24), more males (57). Fifteen cases were vaccinated and 89 unvaccinated. Of 88 hospitalised cases, 31 cases reported stay in Intensive Care Unit (ICU). The median length of hospitalisation was 8 days. Although the variable vaccinated in infants was statistically significant in a univariable analysis for outcome hospitalisation, RR 0.76 (95% CI 0.53-1.10), it was not in multivariable. Hospitalisation was strongly associated with the younger age group of 0-3 months adjusted by a smoking family member in a household (OR = 9.72; 95% CI: 2.97-31.81). Stay in ICU was strongly correlated with the younger age group of 0-3 months (OR = 5.07; 95% CI: 1.44-17.87) and with a contact with confirmed or probable pertussis (OR = 7.05; 95% CI: 1.36-36.52). CONCLUSIONS: Our study demonstrated younger age and contact with other pertussis case as risk factors for hospitalisation of infants with pertussis. It is necessary to consider adolescent and adult boosters, including vaccination during pregnancy. We suggest integrating the variables from the enhanced surveillance system into the nationwide notification system, in order to simplify the data reporting and evaluation. Further studies are needed to evaluate the ESS and to monitor the vaccination of pregnant women against pertussis.
Keywords: Female; Vaccination; infant; vakcinace; whooping cough; novorozenec; Pertussis Vaccine; mužské pohlaví; rizikové faktory; Retrospective Studies; Infant; kojenec; retrospektivní studie; Humans; hospitalisation; doppler ultrasound of uterine artery; Whooping Cough; pertusová vakcína; Czech Republic; risk factors; hospitalizace; těhotenství; pertuse; hospitalization; lidé; ženské pohlaví; Hospitalization; Risk Factors; surveillance; Pregnancy; Česká republika; Infant, Newborn; pertussis; Male